Intravenous Bone Marrow Mononuclear Cells Transplantation Improves the Effect of Training in Chronic Stroke Mice - Ogawa, Yuko; Okinaka, Yuka; Takeuchi, Yukiko; Saino, Orie; Kikuchi-Taura, Akie; Taguchi, Akihiko (Frontiers in Medicine, 2020)
There is no effective treatment for chronic stroke if the acute or subacute phase is missed. Rehabilitation alone cannot easily achieve a dramatic recovery in function. In contrast to significant therapeutic effects of bone marrow mononuclear cells (BM-MNC) transplantation for acute stroke, mild and non-significant effects have been shown for chronic stroke. In this study, we have evaluated the effect of a combination of BM-MNC transplantation and neurological function training in chronic stroke. The effect of BM-MNC on neurological functional was tested four weeks after permanent middle cerebral artery occlusion (MCAO) insult in mice. BM-MNC (1 × 105cells in 100 μl PBS) were injected into the vein of MCAO model mice, followed by behavioral tests as functional evaluations. Interestingly, there was a significant therapeutic effect of BM-MNC only when repeated training was performed. This suggested that cell therapy alone was not sufficient for chronic stroke treatment; however, training with cell therapy was effective. The combination of these differently targeted therapies provided a significant benefit in the chronic stroke mouse model. Therefore, targeted cell therapy via BM-MNC transplantation with appropriate training presents a promising novel therapeutic option for patients in the chronic stroke period.